Journeys in big data statistics - Dryden, Ian L.; Hodge, David J. (Elsevier, 2018)
The realm of big data is a very wide and varied one. We discuss old, new, small and big data, with some of the important challenges including dealing with highly-structured and object-oriented data. In many applications the objective is to discern patterns and learn from large datasets of historical data. We shall discuss such issues in some transportation network applications in non-academic settings, which are naturally applicable to other situations. Vital aspects include dealing with logistics, coding and choosing appropriate statistical methodology, and we provide a summary and checklist for wider implementation.